Immunohistochemistry as a Surrogate Marker of Underlying Molecular Derangements in Sporadic Colorectal Carcinoma in Children – A Series of Three Cases. (7th February 2022) - Maity, Priyanka; Halder, Aniket; Ghosh, Ranajoy; Chatterjee, Uttara; Barman, Shibsankar; Sarkar, Ruchirendra
Abstract: Background: Colorectal carcinomas (CRCs) are uncommon tumors in children. Here, we elucidate three cases of childhood CRCs with their underlying molecular derangements using immunohistochemistry (IHC) with emphasis on BRAF mutation. Case summary: All three CRCs were sporadic tumors involving the left colon with two of them having a mucinous phenotype. We performed IHC for BRAF, p53 and β-catenin along with markers of microsatellite instability (MSI) in all three tumors. All the tumors had diffuse strong cytoplasmic BRAF positivity, with focal p53 positivity in two cases and cytoplasmic β-catenin staining in one case. One case showed CpG island hypermethylation with isolated loss of PMS2 staining. None of the cases had any family history of CRC. Conclusions: IHC can be used as a surrogate marker for determining the underlying molecular derangements in CRC. Sporadic CRCs in children are a cumulative effect of multiple mutations, of which BRAF mutation is significant and critical for planning targeted therapy.